A CONCEPTUAL ANALYSIS OF WOMEN TRAFFICKING AND ITS ORIGIN TYPOLOGY (Andamios, Revista de Investigación Social, 2009)
Recently, migration with trafficking of women has become an important social issue for two reasons: Firstly, because it puts women into the migratory wave, and secondly, because of the violence faced by immigrant woman at the place of destination. Every day thousands of women worldwide are trafficked into cities and other countries with false promises and coercion, basically for the purpose of sexual exploi- Andamios 377 tation. Although trafficking of women is progressively drawing attention worldwide, its lack of conceptual definition makes it hard to distinguish between illegal migration and trafficking. So, the main objective of this study is to develop a clear conceptual definition of women trafficking and to construct a typology considering the patterns of migration from the place of origin to destination.
Keywords: Women trafficking; illegal migration; smuggling; type of movement